A retrospective cohort study to assess adjuvant concurrent chemoradiation (CCRT) compared to adjuvant radiation therapy (RT) in the treatment of grade 2 and 3 extremity soft tissue sarcomas. Issue 1 (October 2017) - Nesseler, Jean Philippe; Salleron, Julia; Rios, Maria; Nickers, Philippe; Marchal, Frederic; Brocard, Fabien; Peiffert, Didier; Vogin, Guillaume
Abstract: Purpose: To evaluate the efficacy and tolerance of adjuvant concurrent chemoradiation (CCRT) as treatment of grade 2 and 3 (G2-3) localized extremity soft tissue sarcomas (STS) by comparing CCRT with standard adjuvant radiation therapy (RT). Patients and methods: This monocentric retrospective study included non-pediatric patients (>16 years) treated by adjuvant RT with or without chemotherapy (CT) after conservative resection of non-recurrent G2-3 extremity STS. Results: A total of 80 patients were treated between 1990 and 2012: 51 by RT and 29 by CCRT. Of the 29 CCRT patients, 25 received doxorubicin monotherapy (75 mg/m 2 /3 weeks). The CCRT group contained a greater proportion of grade 3 extremity STS ( p < 0.001). Median follow up was 68 months (9–284). Multivariate analysis revealed greater local control in the CCRT group (1 local recurrence vs 8 in the RT group; HR = 0.082, 95% CI 0.011–0.321) and incomplete resection as the major risk factor of local recurrence (HR = 25.2, 95% CI 4.767–133.226). The two groups exhibited no differences in distant failure-free survival (HR = 1.469, 95% CI 0.668–3.228), disease-free survival (HR = 1.096, 95% CI 0.519–2.315) or overall survival (HR = 1.378, 95% CI 0.498–3.814). Grade 3 was an adverse prognostic factor for overall survival (HR = 3.11, 95% CI 1.04–9.32). Our analyses also revealed that CCRT tended to increase the risk of both grade ≥3 acute dermatitis (14 events vs 6 in the RT group; OR = 6.99, 95% CI 2.28–21.47) and grade ≥2 late toxicity (6 events vs 3 in the RT group; p = 0.0572). Conclusion: CCRT could improve local control as part of a limb-preservation strategy. However, with a limited number of patients, CCRT showed no improvement in either distant control or survival and increased toxicity.